Instantiations of Multiscale Kinship in Pressing‐Defect Distributions in Yttria‐Stabilized Zirconias by Powder Partitioning - Pereira, Raíssa Monteiro; Lohbauer, Ulrich; Schulbert, Christian; Göken, Mathias; Wurmshuber, Michael; Campos, Tiago Bastos Moreira; Thim, Gilmar Patrocínio; Mieller, Björn; Belli, Renan (Advanced Engineering Materials, 2024)
Modern dry pressing of ceramic powders using spray-dried granulates cannot avoid the occurrence of defects related to persisting inter- and intra-granulate interstitial voids. These constitute the parent defect size population limiting the application of polycrystalline ceramics in high-stress conditions. The mitigation of such defects could widen the range of application in technical and biomedical engineering, reduce the safety range for design, and extend the lifetime of components. Herein, the Weibull size-effect on strength in size-partitioned Yttria-stabilized zirconias (YSZ) feedstocks is used to explore the viability of changing the density distribution of granulate sizes as an effective strategy to obtain a denser particle packing that could reduce the size distribution of strength-limiting pressing defects. In a direct assessment of critical defect size using multiscale strength testing with a dataset of ≈1300 values, the success of such an approach in increasing the strength reliability for small volume components is demonstrated, along with its ultimate failure in altering the defect size distribution in sintered YSZ ceramics across several length scales. Finally, it is shown that granule morphology (spherical or dimpled) fails to affect the defect density and size distribution in YSZ ceramics.<br
Keywords: powder processing; pressing defects; strength; Weibull statistics; zirconia ceramics